Breast decorations from the burials of the Bolshiye Pamyaly burial ground of the XVIII – first half of the XIX century - Voronov Vsevolod V. (Поволжская археология)
The article for the first time publishes materials from the Bolshiye Pamyaly Mari burial ground, discovered in 2022. The paper studies the sul’gams, one of the numerous groups of decorations in the burial set of the burial ground without mounds of the XVIII – midXIX centuries. The relevance of the topic is due to the fact that the depicted patterns can trace the trends of cultural evolution and, at the same time, the continuity of forms with earlier ones. The typology of breast decorations, the basis of which are sul’gams, and their arrangement are considered. The classification of sul’gams uses the method of considering them as parts of breast decorations, considered by T.B. Nikitina according to their functional purpose. Statistical analysis by type indicates a significant predominance of the type II in the burial ground, for functional purpose - decorations. Sul’gams are most often found in burials in the number of one piece, but there are also two. They are not found with male bones. The burial ground is characterized as a monument of Mari culture. In some cases, the shapes and ornamentation of the sul’gams find analogies in the products of neighboring Chuvash and Mordvinian cultures. This decoration in the materials of the burial ground is distinguished by the variability of shapes and patterns.